Exploring the Attitudes and Needs of Advance Care Planning Practice Among the Working Generation - Takako Iwasaki; Ayako Kou; Nozomi Harasawa; Miki Morishita-Kawahara; Chihiro Yamagata; Haruyo Moriya; Mari Ikeda; Hiroko Nagae (Tokyo Women's Medical University Journal, 2022)
Background: This study explores the working generation's attitudes and needs regarding advance care planning and the factors associated with its practice. Methods: This cross-sectional study was conducted through a questionnaire survey with adults working in Kakegawa City, Japan. Logistic regression was used to assess the relationships between advance care planning practices and potential related factors. Results: Of the 182 participants whose data were analyzed, 49.5%, 17.6%, and 2.7% reported having considered, discussed, and documented advance care planning, respectively. The logistic regression analysis showed that advance care planning consideration was associated with three factors: experience of serious accidents/diseases, presence of agencies/persons to consult about medical treatment and care, and willingness to learn about it. Discussion about advance care planning was significantly associated with the following factors: female, experience of serious accidents/diseases, and willingness to learn about it. Due to limited completion rates, documented advance care planning was excluded from the relevant statistics. Conclusions: Incidence of advance care planning among the working generation is low. It might be necessary to create a foundation of related knowledge as well as opportunities for consideration or discussion by which people can understand the need for advance care planning.